Singapore's Housing Policies: 1960-2013 - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2013)
The focus of this case study is on the important role of real estate and housing policies in Singapore’s economic development. In the sphere of housing policy, Singapore is known for its high homeownership rates, the very significant role played by the government in housing supply and housing finance, and the wealth that has been created and distributed in the process.